Hollow spheroids beyond the invasive margin indicate the malignant potential of colorectal cancer. Issue 1 (11th August 2011) - Tamura, Koichi; Yokoyama, Shozo; Ieda, Junji; Takifuji, Katsunari; Hotta, Tsukasa; Matsuda, Kenji; Oku, Yoshimasa; Watanabe, Takashi; Nasu, Toru; Kiriyama, Shigehisa; Yamamoto, Naoyuki; Nakamura, Yasushi; et al.
Abstract : Objective: Tumour budding formed by histologically undifferentiated cancer cells beyond the border of the tumour margin is associated with lymph node metastasis. However, hollow tumour nests, a possible histologically advanced phenotype of tumour budding, have not been discussed. We examined whether hollow spheroids exist beyond the border of the invasive margin and are associated with metastasis and prognosis. Moreover, we suggest that carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1) isoform balance is associated with hollow spheroid formation. Methods: Immunohistochemical analyses with CEACAM1 and M30 as an apoptosis marker were performed to examine the importance of hollow spheroid CEACAM1 expression and central cell apoptosis in hollow spheroid formation. The correlations between the presence of hollow spheroids beyond the invasive margin and the clinicopathological characteristics of 314 patients with colorectal cancer were retrospectively evaluated. A 3D culture with colorectal cancer cells transfected with CEACAM1 cDNA or shRNA was used to determine whether CEACAM1 isoform balance controls colorectal hollow spheroid formation. Results: Hollow spheroid formation accompanying central cell apoptosis was confirmed by M30 staining and serial section with CEACAM1 staining. Of the 314 patients, 96 (30.4%) were classified as having hollow spheroids. The presence of hollow spheroids is an independent risk factor for metastases and shorter survival. In 3D culture, CEACAM1 isoform balance modulated hollow spheroid formation of colorectal cancer cells. Conclusions: Hollow spheroid formation beyond the border of the tumour margin in colorectal cancer is more important than tumour budding for the prediction of malignant potential.